Integration of Accounting and Islamic Education Management in Building Children’s Mental Health for Sustainable Entrepreneurship - Widianti, Hesti; Wisudawati, Tri; Bekti Utomo; Achmad Sadat, Fahad (Journal of Neonatal Surgery, 2025)
Background: The integration of accounting principles and Islamic education management presents a unique opportunity to foster children's mental health, which is pivotal for nurturing sustainable entrepreneurship. In today's rapidly evolving economic landscape, mental resilience and entrepreneurial skills are essential for young individuals. Data from the World Health Organization (2021) indicates that approximately 1 in 7 adolescents experience mental disorders, highlighting the urgent need for effective educational strategies that incorporate mental health awareness. Islamic education, with its holistic approach, offers a framework that not only imparts knowledge but also promotes ethical values and emotional well-being. Methods: This study employs a mixed-methods approach, combining quantitative data from surveys conducted among educators and parents with qualitative interviews from experts in Islamic education and mental health. The survey, which garnered responses from over 500 participants across various educational institutions, aimed to assess the current integration of accounting and Islamic education in curricula. Statistical analysis was performed using SPSS to identify correlations between mental health outcomes and entrepreneurial readiness among children. Additionally, case studies from schools successfully implementing these integrated approaches were analysed to provide practical insights. Results: Preliminary findings suggest a positive correlation between the integration of accounting principles and Islamic education management and improved mental health outcomes among children. Schools that have adopted this integrated approach reported a 30% increase in students' self-reported mental well-being and a 25% improvement in entrepreneurial skills, as measured by a standardised assessment tool. For instance, the Al-Amin School in Jakarta, Indonesia, has implemented a curriculum that blends accounting and Islamic values, resulting in a notable enhancement in students' confidence and problem-solving abilities. Furthermore, interviews with educators revealed that students engaged in this integrated learning environment exhibited greater resilience and adaptability, traits essential for sustainable entrepreneurship. Conclusion: The findings underscore the critical role of integrating accounting and Islamic education management in promoting children's mental health and preparing them for future entrepreneurial endeavours. By fostering a supportive educational environment that prioritises mental well-being alongside practical skills, we can cultivate a generation of resilient and ethically-minded entrepreneurs. This study advocates for policymakers to consider the incorporation of such integrative approaches in educational frameworks, as they hold the potential to significantly impact children's mental health and entrepreneurial capabilities in a sustainable manner.